SCHOPENHAUER’S VOLUNTARISM AND EARLY BUDDHISM: A COMPARATIVE METAPHYSICAL STUDY OF WILL, SUFFERING, AND LIBERATION (Isagoge - Journal of Humanities and Social Sciences, 2026)
This article examines the philosophical relation between Arthur Schopenhauer’s metaphysics of the will and early Buddhist teachings on taṇhā, dukkha, and nibbāna. It argues that both systems diagnose suffering as rooted in restless striving or craving and both associate liberation with the cessation of desire. Yet the article also shows that this similarity has clear limits. Schopenhauer presents the will as the thing in itself and as the inner essence of phenomenal reality, whereas early Buddhism treats craving as a conditioned phenomenon arising through ignorance, feeling, and dependent origination. This distinction has significant consequences for their accounts of liberation. The negation of the will to life in Schopenhauer remains metaphysically tense because the principle to be overcome is also the ultimate ground of appearance. Buddhist liberation, by contrast, follows from the cessation of the conditions that sustain craving. Using comparative hermeneutics, the article clarifies both convergence and divergence across metaphysics, anthropology, ethics, and soteriology. The article contributes to comparative philosophy by showing that Schopenhauer and early Buddhism converge in their existential diagnosis of suffering while diverging in their ontological account of its cause.